2007
DOI: 10.1093/ps/86.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Soybean Meal on Digestive Enzyme Activities and Intestinal Morphology in Broilers

Abstract: The experiment was performed to compare the effects of fermented soybean meal (fermented with Aspergillus oryzae 3.042, FSBM) and soybean meal on digestive enzyme activities and intestinal morphology in broilers. Three hundred twenty 1-d-old Ross x Ross male broiler chicks were randomly allocated into 2 dietary treatments for a 6-wk feeding trial, including 0- to 21-d and 21- to 42-d periods. At the end of each stage, 8 broilers of each treatment were killed, and pancreas, small intestine digesta, and duodenum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 33 publications
6
90
1
1
Order By: Relevance
“…Protein solubility in a KOH solution has been proved a good indicator for monitoring over-processing of soybean meal (Araba and Dale, 1990). Other methods such as chemical treatments (Sessa et al, 1990;Wu and Sessa, 1994), chemical modification of disulfide bonds (Wang et al, 2009), fermentation (Feng et al, 2007) etc. were studied to explore the possibility to inactivate the activity of trypsin inhibitors, however, these methods still stay in research level so far.…”
Section: Approaches Used In Inactivating the Anti-nutritional Factorsmentioning
confidence: 99%
“…Protein solubility in a KOH solution has been proved a good indicator for monitoring over-processing of soybean meal (Araba and Dale, 1990). Other methods such as chemical treatments (Sessa et al, 1990;Wu and Sessa, 1994), chemical modification of disulfide bonds (Wang et al, 2009), fermentation (Feng et al, 2007) etc. were studied to explore the possibility to inactivate the activity of trypsin inhibitors, however, these methods still stay in research level so far.…”
Section: Approaches Used In Inactivating the Anti-nutritional Factorsmentioning
confidence: 99%
“…Study indicated that plant proteins treated with specific proteolytic enzymes could produce particular nutritional ingredients such as bioactive peptides or special amino acids (Schaafsma 2009). Feng et al (2007) reported that soybean peptides promoted the digestive enzyme activities and intestinal morphology in weaned pigs and broilers. Furthermore, in vitro, soybean peptides increased the secretion of insulin and insulin-like growth factor 1 (IGF-1) in NCI-H716 cells (Kwon et al 2011), while IGF-1 could induce Akt/mTOR pathway transcription in mice myoblasts (Latres et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of PSP in the starter diet improved the histomorphology of the small intestine mucosa in terms of villi height, crypt depth villus:crypt ratio and villi surface area as measured at the jejunum at 24 d. The results were in accordance with the findings of Xu et al (2012) who found that the villus height and villus:crypt ratio were increased in the duodenum and jejunum of egg-laying hens on diets supplemented with processed (fermented) soybean meal compared with those receiving plain SBM. Feng et al (2007) observed an improvement in the intestinal morphology of broiler chicks as a result of replacement of untreated SBM with fermented SBM in the starter diet. The improvement in the morphology of intestinal mucosa of chickens fed on PSP-supplemented starter diets may be primarily due to the stimulatory effect of the product.…”
Section: Discussionmentioning
confidence: 91%